2023
DOI: 10.1039/d3sc00181d
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed addition of acylsilanes across alkynesviathe activation of a C–Si bond

Abstract: Palladium-catalyzed addition of a C–Si bond in acylsilanes across the triple bonds in an alkyne bearing a carbonyl group at one terminal is reported. The reaction proceeds with excellent regioselectivity,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In an early study, Narasaka and co-workers reported on the palladium-catalyzed decarbonylative bis-silylation of electron-deficient alkenes or alkynes using a bis-silyl ketone, a reaction that likely proceeds through the oxidative addition process . We previously reported on the palladium-catalyzed addition of a C–Si bond in acylsilanes across allenes and alkynes . (Scheme A).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In an early study, Narasaka and co-workers reported on the palladium-catalyzed decarbonylative bis-silylation of electron-deficient alkenes or alkynes using a bis-silyl ketone, a reaction that likely proceeds through the oxidative addition process . We previously reported on the palladium-catalyzed addition of a C–Si bond in acylsilanes across allenes and alkynes . (Scheme A).…”
mentioning
confidence: 99%
“…The reaction proceeded with complete regioselectivity, where a silyl group is incorporated into the central carbon of the allene moiety while an acyl group is attached to the internal position. The observed regioselectivity is identical to that observed for reactions using nonfluorinated acylsilanes . Monosubstituted allenes, including those bearing alkyl groups (i.e., 5a and 5b ), chlorides (i.e., 5c ), esters (i.e., 5d ) and imides (i.e., 5e ), successfully participated in this silylacylation reaction, providing the corresponding products in a regioselective manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation